The Effects of Endorphin Massage and Deep Breathing Relaxation Techniques on Labor Pain at the Kiswari Private Obstetric Clinic, Central Metro - Iis Tri Utami; Tiara Suci Peronica; Merry Khunchoroyati; Elsy Juni Andri Kariny; Eka Tri Wulandari (Sean Institute, 2026)
Labor pain is a physiological experience reported by nearly all parturient women. Globally, approximately 93.5% of women in labor experience moderate to severe pain, while in Indonesia, the incidence of labor pain reaches 85–90%. In Lampung Province specifically, 37,264 women (approximately 30%) experience high-intensity labor pain. Unmanaged pain can lead to anxiety, fatigue, and prolonged labor. This study aims to determine the effect of endorphin massage and deep breathing relaxation techniques on labor pain at BPM Kiswari Amd.Keb, Central Metro, in 2025. This research employed a quasi-experimental approach with a two-group pretest-posttest design. The study was conducted in July 2025 with a sample of 28 parturient women (14 in the intervention group and 14 in the control group) selected via consecutive sampling. Data were collected using observation sheets and the Numeric Rating Scale (NRS) to measure pain intensity before and after the intervention. Data analysis was performed using the Mann-Whitney U test. The results indicated that the mean pain level in the intervention group decreased from 7.29 (severe pain) to 5.00 (moderate pain), whereas no significant change was observed in the control group. The Mann-Whitney test yielded a p-value of 0.000, indicating a significant effect of endorphine massage and deep breathing relaxation techniques on reducing labor pain. It is recommended that healthcare providers, particularly midwives, implement these techniques as non-pharmacological methods of labor pain management to improve maternal comfort during the birthing process.